(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2017)
Â Â The ZnO/TiO2 bilayer was fabricated on the fluorine-doped tin oxide (FTO) substrate. The ZnO nanorods and TiO2 nanoparticles were developed as photoanode material that were fabricated by using sol-gel immersion and squeegee method. The structure of ZnO/TiO2 bilayer showed a good properties for photoanode in DSSCs application. The ZnO/TiO2 bilayer has large surface area that could increase a dye loading and performance of photoanode. Meanwhile, the micro-Raman spectra of ZnO/TiO2 bilayer indicated a good crystallinity. Therefore, the ZnO/TiO2 bilayer showed a good structure for photoanode in DSSCs application. Key words: ZnO nanorods, TiO2 nanoparticles, ZnO/TiO2 bilayer, Photoanode Â ABSTRAK Lapisan ZnO/TiO2 difabrikasi di atas substrat oksida timah yang di doping florin (FTO). Batang nano ZnO dan partikel nano TiO2 dikembangkan sebagai material fotoanoda yang difabrikasi menggunakan metode pencelupan sol-gel dan squeegee. Struktur lapisan ZnO/TiO2menunjukkan sifat fotoanoda yang baik dalam aplikasi DSSCs. Lapisan ZnO/TiO2memiliki luas permukaan yang besar yang bisa meningkatkan muatan dye dan performa fotoanoda. Sedangkan spktrum mikro-Raman lapisan ZnO/TiO2mengindikasikan kristalinitas yang bagus. Oleh karena itu, lapisan ZnO/TiO2menunjukkan struktur yang baik untuk fotoanoda di dalam aplikasi DSSCs. Kata Kunci: batang nano ZnO, partikel nano TiO2, lapisan ZnO/TiO2, fotoanoda